Selenium and the impact of its supplementation on subclinical hypothyroidism - Natalia Namroży; Julia Dubel; Robert Dubel; Kinga Ruszel; Aleksandra Czekaj (Nicolaus Copernicus University in Toruń, 2022)
Hypothyroidism is a common disease, very often associated with an autoimmune reaction of the body leading to lymphocytic infiltration within the thyroid gland, i.e. Hashimoto's disease. In the classification of disease entities involving the functioning of the thyroid gland, subclinical hypothyroidism can also be distinguished - a condition in which peripheral thyroid hormone concentrations are within normal limits, but as a result of the inhibition of negative feedback loops, the TSH value increases. The subject of this paper is the consideration of the potential impact of selenium supplementation - an element included in bioactivators associated with the thyroid gland, responsible, among others, for the production of an active form of thyroid hormones, for the possibility of achieving euthyroidism in patients with subclinical hypothyroidism, using only rational selenium supplementation, without the use of exogenous thyroid hormones.